Understanding Potential MicrotaskWorkers for Paid Crowdsourcing - Wang, Ming-Hung; Chen, Kuan-Ta; Wang, Shuo-Yang; Lei, Chin-Laung (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
More and more people leverage the power of crowds to obtain solutions of their problems, and the number of microtask workers also increases rapidly on paid crowdsourcing marketplaces. However, there is an order of magnitude discrepancy between the population of Internet users (approximately 2 billions) and that of microtask workers (approximately 0.5 millions); we believe that a large number of potential workers are interested in microtasks but have not involved in paid crowdsourcing activities yet. In this paper, we conduct an Internet survey to investigate potential workers regarding their demographics, experiences in microtasks, preferences on tasks and rewards. We hope that our findings from this research are helpful for establishing a prosperous paid crowdsourcing environment.